Mid-term clinical and radiographic outcomes of PyroDisk interposition arthroplasty for thumb carpometacarpal arthritis: a retrospective case series - Ji-Won Lee; Yang-Guk Chung; Jaehak Lim; Youn-Tae Roh (Archives of Hand and Microsurgery, 2026)
Purpose: Osteoarthritis of the thumb carpometacarpal (CMC) joint is one of the most common hand conditions requiring surgery and predominantly affects postmenopausal women. No surgical technique has consistently demonstrated superiority. The PyroDisk (Integra Life Sciences) interposition implant preserves trapezial bone stock and thumb length, with favorable survival rates reported in Western cohorts; however, data from Asian patients remain limited.Methods: We retrospectively analyzed 33 joints in 32 women with Eaton-Littler stage III thumb CMC osteoarthritis who underwent PyroDisk arthroplasty between 2013 and 2023. The mean age was 63.9 years, and the mean follow-up was 40.8 months. Pain was assessed categorically at final follow-up. Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) scores were available for 22 joints, and grip and pinch strength were compared between the operated and contralateral sides in 23 joints.Results: Pain resolved completely in 19 joints, whereas mild or moderate residual pain persisted in 14 joints. The mean QuickDASH score was 20.9±16.2. Grip and pinch strength recovered to 91.9% and 99.1% of the contralateral side, respectively (p=0.057 and p=0.381). The implant retention rate was 100% (33/33), and patient satisfaction was 93.5%. Radiographic displacement was not significantly associated with clinical instability (p=0.053).Conclusion: PyroDisk arthroplasty provided favorable pain and functional outcomes in Korean patients with advanced thumb CMC osteoarthritis, with complete implant retention at mid-term follow-up. These findings are broadly consistent with those of Western cohorts and support PyroDisk arthroplasty as a viable surgical option for advanced thumb CMC osteoarthritis in selected Asian patients.